Is it worth to recuperate degraded pasturelands? An evaluation of profits and costs from the perspective of livestock producers and extension agents in Honduras - Holmann, Federico J.; Argel M., Pedro J.; Rivas Ríos, Libardo; White, D.; Estrada, R.D.; Burgos, C.; Pérez, E.; Ramírez, G.; Medina, A. (2004)
The objectives of this study were to: (a) estimate milk and beef yields obtained from cows grazing pastures in different stages of degradation; (b) estimate income losses as a result of the degradation process; (c) estimate the proportion of pasture areas found in each stage of degradation within the six administrative regions of Honduras; and (d) identify different strategies and costs to recuperate degraded pastures. Data came from two surveys executed during a workshop carried out in March 2004. The subjective perceptions of 25 livestock producers and 8 extension agents of the 6 administrative regions of Honduras were obtained to estimate the losses of animal productivity within the farm, region, and country. A 4-level scoring of pasture degradation was defined -- where 1 was for the best condition (i.e., non-apparent degradation) and 4 was for the worst (i.e., severe degradation). Regressions, explaining the animal productivity losses at each level of pasture degradation, were generated according to the subjective and descriptive information. Comparing the perception of degraded areas, producers considered that in Honduras the extent of pasture degradation is lower compared with extension agents. According to producers, 29% of the pasture area in the country is at Level 1 (i.e., no degradation) compared with only 19% of extension agents. Moreover, producers perceived a lower proportion of pastures in severe degradation (i.e., Level 4, 27%) in comparison with almost 31% perceived by extension agents. In the intermediate degradation levels (i.e., Levels 2 and 3), both groups were similar. The country is forgoing milk and beef production due to the process of pasture degradation. According to estimations from producers, Honduras is loosing 284,106 tonnes of fluid milk and 48,271 tonnes of beef (live weight) annually for having pasture areas in Level 4 (i.e., severe degradation), equivalent to 48% of the annual production of milk and to 37% of beef. In economic terms, these losses in milk and beef yields are worth US$63 and US$48 million annually, respectively. The perception of extension agents is even more alarming. Honduras could produce 66% more milk and 50% more beef annually if livestock producers renovated their pastures before they reached level 4, equivalent to US$94 million in less revenues from milk sales and US$66 million from less beef sales. Both groups perceive that pastures, in an early stage of degradation (i.e., Level 2), are more economical, practical and rapid to recuperate. Also, as the process of degradation advances (i.e., to Levels 3 and 4), both cost and time of recuperating such pastures increase significantly. According to producers, the recuperation of a pasture from Level 4 to Level 1 costs $140/ha and takes almost a half year (i.e., 5.6 months). Extension agents estimate this cost of recuperation 27% higher ($178/ha) with 5% more time (i.e., 5.9 months). Producers perceive that grasses spend proportionately less time in going from Level 1 to 2 (i.e., 2.9 years) and as the process of degradation continues, pastures remain longer at advanced degraded levels (i.e., 3.1 years in going from level 2 to 3, and around 4.0 years in going from level 3 to 4). Moreover, producers think that the average productive life of improved grasses is about 10 years, while extension agents think that grasses degrade faster, with an average productive life of 8.4 years, 16% less than producers. According to producers and extension agents, pastures degrade at an annual rate of 10% and 12%, respectively. With these rates, Honduras would maintain its current level of degradation between levels 2.48 and 2.65. However, the renovation of pastures at an annual rate of 10-12% does not solve the problem, but maintains it. Producers argued that the current financial situation does not allow the necessary cash flow to renovate their plots, and the option of credit is not viable since real interest rates are high (ie., 10%). After simulating this scenario, it was demonstrated that farmers are able to generate the additional income necessary to pay a credit, but only if this credit is taken with interest rates similar to those found in the international market (ie., 3%). In order to eliminate the degraded areas found in Level 4 at the country level, it is necessary a one-time investment of $57 million according to producers and $84 million according to extension agents. The benefit obtained from this investment would result in a daily increase of 156,000 liters of milk and 26,500 kilograms of beef, equivalent to $22 millions/yr. Therefore, there are significant economic and productive incentives for the private and public sectors to develop and execute a plan of action to recuperate pasturelands in advanced stages of degradation.